Meta-Analysis of the Effects of the Catechol-O-Methyltransferase Val158/108Met Polymorphism on Parkinson’s Disease Susceptibility and Cognitive Dysfunction - Tang, Chuanxi; Wang, Wei; Shi, Mingyu; Zhang, Na; Zhou, Xiaoyu; Li, Xue; Ma, Chengcheng; Chen, Gang; Xiang, Jie; Gao, Dianshuai (Frontiers in Genetics, 2019)
ackground: There is the continued debate and inconsistent findings in the previous literature about the relationship of COMT and PD susceptibility as well as cognitive dysfunction. To comprehensively examine COMT genotype effects on the development of Parkinson’ disease and test the hypothesis that the Met158 allele of the COMT gene is associated with cognitive dysfunction, we conducted a meta-analysis review to substantiate this existing gap. Methods PubMed/MEDLINE, Embase, Cochrane databases search (18/30/08) yielded 49included studies. Data were extracted by two reviewers and included COMT genotype, publication year, diagnostic status, ancestry, proportion of male participants, and whether genotype frequencies were consistent with Hardy-Weinberg equilibrium. Unadjusted odds ratios (ORs) were used to derive pooled estimates of PD risk overall and in subgroups defined by ethnicity, gender, onset of PD. Moreover, the association of certain cognitive domains in PD and COMT gene type was explored. Meta-analyses were performed using random-effect models and p-value based methods. All statistical tests were two-sided. The present study was registered with PROSPERO (CRD42018087323). Results: In the current studies, we found no association between COMT Val158/108Met polymorphism and Parkinson’s disease susceptibility. However, the gender stratified analyses revealed marginal significance effects in heterozygote model analyses in women (P = 0.053). In addition, stratification according to onset of PD also shows significant effects of COMT Val158/108Met polymorphism on late onset population both in recessive (P=0.017) and allelic (P=0.017) genetic models. For the IQ score and UPDRS III, there was no evidence for genetic association, but the effect size was significantly association in Asian population (IQ score: P = 0.016, UPDRS III:P＜0.001) than Caucasians population. Conclusion: The COMT Val158/108Met polymorphism is associated with the risk for PD in female or late population. Met/Met carriers of Asian population performed significantly worse than the Val allele carriers in IQ score and UPDRS III.